Stronger at Every Age: Together Against Non-Communicable Diseases - Olufunke Ajeigbe; Hawawu Hussein; Phidelia Theresa Doegah; Andrew Matchado; Twaambo Euphemia Hamoonga (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Lifelong health is profoundly shaped by our earliest environments. The Developmental Origins of Health and Disease (DOHaD) framework demonstrates how health, nutrition and nurture from preconception through adolescence determine the trajectory of wellbeing and the risk of noncommunicable diseases (NCDs) in adulthood. Africa offers a unique lens for examining how nations can intervene early to curb the future burden of NCDs. Across Africa, this understanding arrives at a critical juncture. As the continent faces a rising tide of NCDs, its children, adolescents, and families still hold the power to reshape their lifelong health destinies. Amid rapidly changing social and nutritional landscapes, schools emerge as pivotal platforms for prevention amongst other strategies involving health systems and innovative technologies. Embedding DOHaD principles into school-based health education, by emphasizing optimal nutrition, informed parenting, and the life-long benefits of breastfeeding can equip young people with the knowledge and agency to protect their own health and that of future generations. By translating scientific evidence into culturally grounded, community-driven action, we can cultivate health-literate, resilient societies that thrive free from preventable diseases. Investing in early-life interventions and multisectoral partnerships transforms the fight against NCDs from a reactive struggle to a collective opportunity for health, equity, and sustainable development to ensure that every generation grows stronger at every age united against the lifelong shadow of NCDs.